Administrative and sociological variables as correlates of athletes’ performance in Nigeria school sports federation in North-Central States, Nigeria - Kayode, Falaye Elijah; Tunrayo, Ajadi Memunat; Owolabi, Abdulraheem Yinusa; Adesoye, A. A. (International Journal of Educational Innovation and Research, 2022)
This study examined administrative and sociological variables as correlates of athlete's performance in Nigeria School Sports Federation in North-Central States, Nigeria. The objectives of the study were to: (i) determine the relationship between parental influence and athletes performance in NSSF competition (ii) ascertain the relationship between funding and athlete's performance in NSSF competition. Descriptive design of correlation type was adopted for the study. The population for the study comprised sports officers, coaches and NSSF coordinators. Purposive and proportionate random sampling techniques were used to select 585 respondents. Validated researcher designed structured questionnaire which was tested for reliability with a reliability coefficient of 0.80 was used for data collection. Pearson Product Moment Correlation was used for data analysis at 0.05 alpha level. The result of the findings: there was a significant relationship between parental influence and athletes performance in NSSF competition, there was a significant relationship between funding and athletes performance in NSSF competition. The study concluded that sports officers, coaches and NSSF coordinators contributed to brilliant performance of athletes in Nigeria's school sports federation in North-central states Nigeria. The implication is that sports officers, NSSF coordinators and coaches play critical roles in achieving the excellent performance of athletes in school sports competition.